Limb Pain as Unusual Presentation of a Parietal Intraparenchymal Bleeding Associated with Crack Cocaine Use: A Case Report - Alan Lucerna; James Espinosa; Taimur Zaman; Risha Hertz; Douglas Stranges (Case Reports in Neurological Medicine)
Limb pain as a presenting feature of an ischemic or hemorrhagic stroke is extremely rare. Here we present a case of a 65-year-old male with complaints of left arm pain and allodynia (specifically light touch to any part of the left arm produced significant discomfort) who was found to have a right parietal lobe intraparenchymal bleed after smoking crack cocaine. Acute central pain is mainly associated with parietal, thalamic, and brainstem lesions. It has been proposed that acute limb pain from a parietal lobe stroke is due to the disconnection of the parietal cortex from the thalamus secondary to the interruption of the pathways between the hemisphere and thalamus/basal ganglia.